N-Glycolylneuraminic Acid (Neu5Gc) Null Large Animals by Targeting the CMP-Neu5Gc Hydroxylase (CMAH) - Perota, Andrea; Galli, Cesare (Frontiers in Immunology, 2019)
The two major sialic acids described in mammalian cells are the N-glycolylneuraminic acid (Neu5Gc) and the N-acetylneuraminic acid (Neu5Ac). Neu5Gc synthesis starts from the N-acetylneuraminic acid (Neu5Ac) precursor modified by an hydroxylic group addiction catalysed by CMP-Neu5Ac hydroxylase enzyme (CMAH). In humans, CMAH was inactivated by a 92 bp deletion occurred 2-3 Millions years ago. Few other mammals do not synthetise Neu5Gc, however livestock species used for food production and as a source of biological materials for medical applications carry Neu5Gc. Traces amounts of Neu5Gc are uptaken through the diet and incorporated into various tissues including epithelia and endothelia cells. Humans carry natural anti-Neu5Gc antibodies and when undertaking medical treatments that contain animal derived product they can cause immunological reaction against Neu5Gc and severe side effect like serum sickness disease (SSD). Neu5Gc null mice have been the main experimental model to study such phenotype. With the recent advances in genome editing, pigs and cattle KO for Neu5Gc have been generated always in association with the αGal KO. These large animals are normal and fertile and provide additional experimental models to study such mutation. Moreover they will be the base for the development of new therapeutic applications like polyclonal IgG immunotherapy, Bioprosthetic Heart Valves, cells and tissues replacement.